Pengembangan Aplikasi Manajemen Proyek Perangkat Lunak Berbasis Scrum Studi Kasus CV. Nusantara Media Mandiri (CVNMM) - Muhammad Faisal Fahat; Bayu Priyambadha; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Project manager who can handle three to five projects at once, has problems to monitor works of the projects, because in one project there are at least 30 works to be managed. With all of those works, there are works that are not monitored, so they are not completed on schedule. Moreover, CV. Nusantara Media Mandiri (CVNMM) still use waterfall approach in software development. Whereas CVNMM has a policy whereby software that has been completed by the project team, it will get a warranty (software usage training, repair, and changes to the system) for 2 months after the software received by the client. Because of this warranty, especially in case of system changes, just in January - March 2017 there are 4 of 7 clients who request a system change on the software that has been completed by the project team. Therefore, CVNMM wants to develop a software project management application to assist in monitoring works of the project, in addition to dealing with system changes, CVNMM can use the popular agile approach, which is scrum. Because this framework allows the client to review a piece of software, when the developer has finished iterating, so there's no need to wait until the software is completely done. CVNMM's software project management application have 38 functional requirements, where all of the functional requirements have valid in black-box testing.